Muscone improves hypoxia/reoxygenation (H/R)-induced neuronal injury by blocking HMGB1/TLR4/NF-κB pathway via modulating microRNA-142 - Weihua Ren; Fucheng Zhao; Yanru Han; Zhenzhou Liu; Jianli Zhai; Kui Jia (PeerJ, 2022)
Previous reports have indicated that natural muscone has neuroprotective effects against cerebral hypoxia injury; however, little is known in regards to its pharmacological mechanism. In this study, we tried to evaluate the neuroprotective effects and mechanisms of muscone against cerebral hypoxia injury using an in vitro model. The cerebral hypoxia injury cell model was produced by hypoxia/reoxygenation (H/R). The cell viability and apoptosis were measured using the cell counting Kit-8 and the Annexin V-FITC/PI Apoptosis Detection kit, respectively. To screen microRNAs regulated by muscone, we analyzed the gene expression datasets of GSE84216 retrieved from gene expression omnibus (GEO). Here, it was demonstrated that muscone treatment significantly alleviated the cell apoptosis, oxidative stress and inflammation in H/R-exposed neurons. Subsequently, through analyzing GSE84216 from the GEO database, miR-142-5p was markedly upregulated by treatment of muscone in this cell model of cerebral hypoxia injury. Further experiments revealed that downregulation of miR-142-5p eliminated the neuroprotective effects of muscone against H/R induced neuronal injury. Additionally, high mobility group box 1 (HMGB1), an important inflammatory factor, was identified as a direct target of miR-142-5p in neurons. Meanwhile, we further demonstrated that muscone could reduce the expression of HMGB1 by upregulating miR-142-5p expression, which subsequently resulted in the inactivation of TLR4/NF-κB pathway, finally leading to the improvement of cell injury in H/R-exposed neurons. Overall, we demonstrate for the first time that muscone treatment alleviates cerebral hypoxia injury in in vitro experiments through blocking activation of the TLR4/NF-κB signaling pathway by targeting HMGB1, suggesting that muscone may serve as a potential therapeutic drug for treating cerebral hypoxia injury.